Naturalizing Rhetorical Genres in Al-Sijilmasi’s Thought The Genre of Al-Ijaz as a Case Study/ تجنيس المعنى البلاغي لدى السجلماسي جنس الإيجاز أُنموذجاً - Nuhad Mutlib Mukhlif; Amer Mhidi Salih; Abdul-Nasir Hashim Mohammed (Ijaz Arabi Journal of Arabic Learning, 2026)
The rhetorical significance that this research seeks to uncover lies in the universal law (al-Qānūn al-Kullī) that Al-Sijilmāsī aimed to establish within the genre of conciseness (al-Ījāz). This principle serves as the general governing rule and the fundamental backbone of this genre. It represents a systematic trend governing the various rhetorical sub-types branching from the genre of conciseness, which share common rhetorical characteristics qualifying them to fall under a single 'High Genre' (Jins 'Ālī).In this study, we examine the rhetorical meaning within this genre, into which Al-Sijilmāsī categorized a set of Arabic rhetorical devices, without claiming to have exhausted all possible styles. His primary objective was to demonstrate the general law of rhetorical meaning rather than to provide an exhaustive inventory of styles. The research argues that the High Genre of conciseness represents a cornerstone that sheds light on a vital aspect of general rhetorical meaning, such as the duality of expression and meaning (al-lafẓ wa-al-ma‘nā) that governed this genre.